Toxic effects of mercury on the cell nucleus of Dictyostelium discoideum. Issue 2 (16th February 2016) - Boatti, Lara; Rapallo, Fabio; Viarengo, Aldo; Marsano, Francesco
ABSTRACT: Governmental agencies (www.epa.gov/mercury ) and the scientific community have reported on the high toxicity due to mercury. Indeed, exposure to mercury can cause severe injury to the central nervous system and kidney in humans. Beyond its recognized toxicity, little is known regarding the molecular mechanisms involved in the actions of this heavy metal. Mercury has been also observed to form insoluble fibrous protein aggregates in the cell nucleus. We used D. discoideum to evaluate micronuclei formation and, since mercury is able to induce oxidative stress that could bring to protein aggregation, we assessed nuclear protein carbonylation by Western Blot. We observed a significant increase in micronuclei formation and 14 carbonylated proteins were identified. Moreover, we used isotope‐coded protein label (ICPL) and mass spectrometry analysis of proteins obtained by lysis of purified nuclei, before of tryptic digestion to quantify nuclear proteins affected by mercury. In particular, we examined the effects of mercury that associate a classical genotoxic assay to proteomic effects into the nucleus. The data present direct evidences for mercury genotoxicity, nuclear protein carbonylation, quantitative change in core histones, and the involvement of pseudouridine synthase in mercury toxicity. © 2016 Wiley Periodicals, Inc. Environ Toxicol 32: 417–425, 2017.